OPTIMASI SUCKER ROD PUMP PADA SUMUR “RA” DI LAPANGAN “RZA” UNTUK PERAWATAN KINERJA SUMUR - Reza Saputra Amang; Rohima Sera Afifah; Muhammad Nur Mukmin; Abdi Suprayitno; Aris Luqman Tryna; Rizky Kurniawan (PETROGAS: Journal of Energy and Technology, 2026)
This research discusses the utilization of Sucker Pump Optimization on the “RA” Well in the “RZA” Field to Maintain Well Performance. Sonolog data were used to determine the Static Fluid Level (SFL), Working Fluid Level (WFL), and bottom-hole pressure, while production data were applied in generating the Inflow Performance Relationship (IPR) curve using the two-phase Vogel equation. The analysis results indicate that the well has a maximum flow rate (Qmax) of 386.905 bpd, while the optimum flow rate (Qoptimum) is 308.43 bpd. Evaluation of the SRP performance shows a pump efficiency of 68%, indicating the need for optimization. Several optimization scenarios were developed by adjusting the strokes per minute (SPM) and stroke length (SL). Among the evaluated scenarios, the best option is Scenario 1, which maintains the pump operation at 9 SPM, resulting in a pump displacement of 308.43 bpd, closely matching the Qoptimum. This scenario is considered the most effective for sustaining stable production without causing excessive reservoir depletion.